2020
DOI: 10.3389/fpls.2020.00062
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Flood-Induced Stress in Soybeans

Abstract: Despite the detrimental impact that excess moisture can have on soybean (Glycine max [L.] Merr) yields, most of today's crop models do not capture soybean's dynamic responses to waterlogged conditions. In light of this, we synthesized literature data and used the APSIM software to enhance the modeling capacity to simulate plant growth, development, and N fixation response to flooding. Literature data included greenhouse and field experiments from across the U.S. that investigated the impact of flood timing and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 57 publications
2
42
0
Order By: Relevance
“…Nowadays, climate change is among the principal factors causing a decline in agricultural productivity. Drought, salinity, low/high temperatures, flooding, acidic conditions and nutrient starvation are the world's most dominant abiotic stresses, also affecting soya bean yield (Arora & Tewari, 2016;Carrera & Dardanelli, 2016;Jumrani & Bhatia, 2018;Pasley, Huber, Castellano, & Archontoulis, 2020;Pathan et al, 2014). Low temperatures are one of the most important limitations of crop productivity, as it has been shown that temperature and the duration of chilling stress affect the mode of action and intensity of plant responses (Ercoli, Mariotti, Masoni, & Arduini, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, climate change is among the principal factors causing a decline in agricultural productivity. Drought, salinity, low/high temperatures, flooding, acidic conditions and nutrient starvation are the world's most dominant abiotic stresses, also affecting soya bean yield (Arora & Tewari, 2016;Carrera & Dardanelli, 2016;Jumrani & Bhatia, 2018;Pasley, Huber, Castellano, & Archontoulis, 2020;Pathan et al, 2014). Low temperatures are one of the most important limitations of crop productivity, as it has been shown that temperature and the duration of chilling stress affect the mode of action and intensity of plant responses (Ercoli, Mariotti, Masoni, & Arduini, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…It includes many crop models along with soil water, C, N, crop residue modules, which all interact on a daily time step. In this project, we used the APSIM maize version 7.9 and in particular the calibrated model version for US Corn Belt environments as outlined by Archontoulis et al 1 that includes simulation of shallow water tables and inhibition of root growth due to excess water stress 38 and waterlogging functions 39 . Within APSIM we used the following modules: maize 40 , SWIM soil water 41 , soil N and carbon 42 , surface residue 42 , 43 , soil temperature 44 and various management rules to account for tillage and other management operations.…”
Section: Methodsmentioning
confidence: 99%
“…We configured APSIM version 7.9 with a series of modules, including maize (Keating et al., 2003), surfaceOM (Probert, Dimes, Keating, Dalal, & Strong, 1998; Thorburn, Meier, & Probert, 2005; Thorburn, Probert, & Robertson, 2001), manager (Keating et al., 2003), biochar (Archontoulis et al., 2016), soiltemperature2 (Campbell, 1985; Dietzel et al., 2016), and SoilWat (Probert et al., 1998). The model accounted for shallow water table fluctuations in this field (Archontoulis et al, 2020) and included recent waterlogging additions made to the model (Ebrahimi‐Mollabashi et al., 2019; Pasley, Huber, Castellano, & Archontoulis, 2020). We used soil profile information from SSURGO (USDA‐NRCS, 2019), which we updated with measurements of soil C in the 0–5 and 5–15 cm depths.…”
Section: Methodsmentioning
confidence: 99%